2012
DOI: 10.1016/j.bbamem.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Surface modified liposomes by mannosylated conjugates anchored via the adamantyl moiety in the lipid bilayer

Abstract: The aim of the present study was to encapsulate mannosylated 1-aminoadamantane and mannosylated adamantyltripeptides, namely [(2R)-N-(adamant-1-yl)-3-(α,β-d-mannopyranosyloxy)-2-methylpropanamide and (2R)-N-[3-(α-d-mannopyranosyloxy)-2-methylpropanoyl]-d,l-(adamant-2-yl)glycyl-l-alanyl-d-isoglutamine] in liposomes. The characterization of liposomes, size and surface morphology was performed using dynamic light scattering (DLS) and atomic force microscopy (AFM). The results have revealed that the encapsulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…[42] In our previous research, we have shown how adamantane can be used as a membrane anchor in lipid bilayer for different carbohydrate molecules which are exposed on liposome surface. [30,43] The obtained results have confirmed that Con A successfully recognized mannosyl ligands exposed on liposome surface and exhibits higher affinity to multivalent mannosyl ligands. [31] Here, we report preparation and characterization of mannosylated liposomes with/without built-in peptidoglycan based immunomodulators, PGM or Ad2TP2, and with entrapped model antigen, ovalbumin.…”
Section: Preparation Of Mannosylated Liposomessupporting
confidence: 69%
See 1 more Smart Citation
“…[42] In our previous research, we have shown how adamantane can be used as a membrane anchor in lipid bilayer for different carbohydrate molecules which are exposed on liposome surface. [30,43] The obtained results have confirmed that Con A successfully recognized mannosyl ligands exposed on liposome surface and exhibits higher affinity to multivalent mannosyl ligands. [31] Here, we report preparation and characterization of mannosylated liposomes with/without built-in peptidoglycan based immunomodulators, PGM or Ad2TP2, and with entrapped model antigen, ovalbumin.…”
Section: Preparation Of Mannosylated Liposomessupporting
confidence: 69%
“…[21][22][23][24][25][26][27] Our previous studies have been focused on the synthesis of novel immunomodulators and potent adjuvant formulations with improved activity. [28][29][30] In recently published paper we described the synthesis of mono-, di-and tetramannosyllipoconjugate, used for mannosylation of liposomes, and studies of interaction of prepared mannosylated liposomes with model lectine, concanavaline A (Con A) by quartz crystal microbalance (QCM). [31] Here we report preparation of mannosylated liposomes with built-in peptidoglycan based immunomodulators, peptidoglycan monomer surface.…”
mentioning
confidence: 99%
“…Our previous research of biologically active adamantoylated compounds has been focused on their interaction with model biological membrane . Although the effect of ferrocene on liposome has not been studied intensively, several recent papers have described the application of oxidized ferrocene as an organometallic amphiphile and ferrocene‐modified phospholipid in preparation of the redox‐modified liposomes .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous research of adamantane derivatives of biologically active peptidoglycan fragments has shown their strong interaction with lipid membrane . Furthermore, we have shown that the adamantyl moiety can be employed as an anchor in the lipid bilayer while the polar part of the molecule, a carbohydrate mannose or guanidine residue, is exposed on the liposome surface …”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies of chemical syntheses and characterization of mannosyl derivatives of biologically active peptidoglycan fragments, namely adamantyltripeptides , have shown their strong interaction with cell membranes and the potential for preparation of glycosylated carriers for drug delivery Štimac et al, 2012). In the continuation of our studies our interest is in finding a potent targeted delivery vehicle for drugs, especially for subunit vaccines with built-in small molecule immunopotentiators.…”
Section: Introductionmentioning
confidence: 96%